CORRELATION BETWEEN METACOGNITIVE STRATEGY, FOREIGN LANGUAGE APTITUDE AND MOTIVATIONS IN LANGUAGE LEARNING - Novia Tri Febriani (Jurnal Bahasa Lingua Scientia, 2017)
Language learning belief and language learning strategies are two essential predictors that have significant effect toward students’ language proficiency. Learners’ belief is dealing with what comes from inside the learners in learning the language, such as foreign language aptitude; difficulty of language learning; nature of language learning; learning and communication strategies; and motivation. Meanwhile, language learning strategies are learners’ plan in achieving certain goals or mastering the target language. A preliminary research was conducted in order to find what strategy mostly used by the learners. It turned out that the strategy mostly used by them was metacognitive strategies. Thus, this study aims to investigate about the correlation between metacognitive strategies and certain belief’ variables in students’ language learning which are foreign language aptitude and motivation. Moreover, twenty postgraduate students of English education department participated in this study. This study used correlational research, in which the BALLI (Beliefs about Language Learning Inventory) and SILL (Strategies Inventory for Language Learners) questionnaires were adopted as the instruments in collecting the data. The findings of this study indicated that there is negative linear correlation between metacognitive strategy and foreign language aptitude (rXY = -0,049) while there is significant positive linear correlation between metacognitive and motivation (rXY =+0,79) in students’ language learning. Furthermore, this study also provide some recommendations, which is it is expected that there will be more researches use studies using different respondents with various contexts. Secondly, the further research will use both of quantitative and qualitative data relating to this issue in order to make a more accurate data.